Factors Affecting Selection of a Dialysis Modality in Elderly Patients With Chronic Kidney Disease: A Prospective Cohort Study in Korea - Cho, Jang-Hee; Lim, Jeong-Hoon; Park, Yeongwoo; Jeon, Yena; Kim, Yon Su; Kang, Shin-Wook; Yang, Chul Woo; Kim, Nam-Ho; Jung, Hee-Yeon; Choi, Ji-Young; Park, Sun-Hee; Kim, Chan-Duck; et al. (Frontiers in Medicine, 2022)
Background: We investigated factors associated with the selection of a dialysis modality for elderly patients compared to younger patients. Methods: This study included 2,514 incident dialysis patients from a Korean multicenter prospective cohort. Multivariate logistic regression analyses were performed with demographic, socioeconomic, and clinical data to analyze factors associated with the chosen dialysis modality. Differences in these factors were compared between the elderly (≥65 years) and younger (<65 years) patients. Results: Of the enrolled patients, 1,746 (69.5%) and 768 (30.6%) selected hemodialysis (HD) and peritoneal dialysis (PD), respectively. The percentage of PD was higher in younger patients than in elderly patients (37.1% vs. 16.9%, p < 0.001). Multivariate analysis showed that planned dialysis (p < 0.001), employment status (p < 0.001), and independent economic status (p = 0.048) were independent factors for selecting PD, whereas peripheral vascular disease (p = 0.038) and tumor (p = 0.010) were factors for selecting HD in the younger group. In the elderly group, planned dialysis (p < 0.001) and congestive heart failure (CHF; p = 0.002) were associated with choosing PD; however, tumor (p = 0.006) was associated with choosing HD. A two-way ANOVA showed that planned dialysis and CHF showed a significant interaction effect with age on modality selection. Conclusions: As the age of patients with chronic kidney disease increased, HD was more frequently selected compared to PD. Dialysis planning and CHF interacted with age in selecting dialysis modalities in elderly patients. Elderly patients were less affected by socioeconomic status than younger patients.